Knowledge management maturity contributes to project-based companies in an open innovation era - Leandro Pereira; António Fernandes; Mariana Sempiterno; Álvaro Lopes Dias; Renato J. Lopes da Costa; Nelson J. dos Santos António (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Knowledge is a crucial asset for any organization nowadays. Despite the temporary nature of projects, proper knowledge management can improve outcomes and benefit future endeavors. However, an effective knowledge management system has to be tailored to each organization. Therefore, it is extremely important to assess the stage of knowledge management (KM) maturity of an organization. The present study analyzed the general maturity level of European projectbased organizations. The analysis was performed to understand the maturity of the knowledge management cycle's phases and it was possible to distinguish which phases were more developed and what are the main steps to create effective organizational learning in a project-based organization. Overall, European-based project-oriented organizations are halfway through the implementation of KM systems. While the need for a proper system has already been acknowledged, the infrastructure to support it still needs to be developed so proper measures can be put in practice.
Keywords: 650; knowledge management; project management; maturity models; organization learning; open innovation